Urban Structures and Crime - Hermann, Dieter (SIAK-Journal, 2010)
Understanding the broken windows approach as an ecological theory focussing on the interrelationships of urban structures and crime, it can be summarized by the following hypotheses: (a) Worsening urban structural conditions lead to higher crime rates, higher fear of crime and to worse perception of quality of life. (b) An increase of delinquency rates, fear of crime and perceived negative quality of life in a district leads to migration and a change in the structural conditions. In this study cross-sectional data, representative surveys, and also longitudinal data about structural changes in German cities were used. The results largely confirm the broken windows approach; however, a modification should be taken into consideration. A supplementing of this approach can be reached by a combination with lifestyle approaches. Following this, crime rates in a district not only depend on structural variables, but also on the lifestyle of the inhabitants.